Penggunaan Souda, Youda, Rashii pada Kalimat Bahasa Jepang - Wijayanthi, Rina Devi; Meidariani, Ni Wayan; Aritonang, Betty Debora (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 6 No 1 (2024)DO - 10.24843/JS.2024.v06.i01.p02, 2024)
This research aims to find out and examine the use of sentences containing souda, youda, rashii in Japanese sentences. The theory used in this research is Prof.'s structural syntax theory. Dr. H. Abdul Muis Ba'dulu, M.S. The data used in writing the article were obtained from Japanese language news sites. Data analysis was performed using descriptive qualitative research techniques. Based on the results of the study it was found that souda, youda, rashii could be used to predict events based on what the speaker felt, saw, and experienced. However, only Souda and Youda can predict something that is based on subjective reasons, while Rashii must use objective reasons when making a guess.